Trading stocks following sharp movements in the USDX, GBP/USD, and USD/CNY - Yensen Ni; Min-Yuh Day; Paoyu Huang (Financial Innovation, 2020)
We hypothesized that sharp movement in the USDX, GBP/USD, and USD/CNY might result in stock market fluctuations owing to heightened investors' sentiments. The subsequent performance of trading stocks right after such sharp movements in exchange rates is seldom explored in existing studies. We examined the historical data of the constituent stocks of the DJ 30, FTSE 100, and SSE 50 indexes and found that the share prices were more volatile after sharp movements in the CNY, even though the currency is less volatile because of China's exchange rate policy. However, for the USD and GBP, share prices of the DJ 30 and FTSE 100, respectively, rose after sharp appreciation and depreciation of the currencies.
Keywords: 650; Investing strategies; Exchange rates; Investors' sentiments